(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
This paper aims to reflect the reality of the Tuquerreña company immersed in the tourism sector in accordance with the incipient accounting and financial processes that are applied today to record the different economic operations. There is no database that allows structuring an X-ray of the current situation of the companies that are dedicated to providing tourist services in the municipality of Túquerres in accounting and financial matters. It’s seeks to identify the accounting processes that are being applied in small and medium-sized companies in the tourism sector in the municipality of Túquerres (N). A survey was applied to a sample made up of 94 people from whom valuable knowledge was obtained to understand the phenomenon under study. The absence of well-defined accounting processes that generate certain shortcomings in the finances of the tourism company in the municipality of Túquerres is identified. It is necessary that improvement and improvement actions be carried out in the accounting and financial processes of this type of organization in order to promote the growth and sustainability of this economic sector.